Days of Gold a Novel - Deveraux, Jude (New York : Atria Books, 2009)
The second book in the multi-generational Edilean series, Days of Gold is a romance set in Scotland in 1766.
Series statement from book jacket.
Keywords: Scotland; Love stories; Historical fiction